Characterization of a Diffusible Signaling Factor from Xylella fastidiosa - Ellen D. Beaulieu (American Society for Microbiology, 2013)
ABSTRACT Cell-cell signaling in Xylella fastidiosa has been implicated in the coordination of traits enabling colonization in plant hosts as well as insect vectors. This cell density-dependent signaling has been attributed to a diffusible signaling factor (DSF) produced by the DSF synthase RpfF. DSF produced by related bacterial species are unsaturated fatty acids, but that of X. fastidiosa was thought to be different from those of other taxa. We describe here the isolation and characterization of an X. fastidiosa DSF (XfDSF) as 2(Z)-tetradecenoic acid. This compound was isolated both from recombinant Erwinia herbicola expressing X. fastidiosa rpfF and from an X. fastidiosa rpfC deletion mutant that overproduces DSF. Since an rpfF mutant is impaired in biofilm formation and underexpresses the hemagglutinin-like protein-encoding genes hxfA and hxfB, we demonstrate that these traits can be restored by ca. 0.5 µM XfDSF but not by myristic acid, the fully saturated tetradecenoic acid. A phoA-based X. fastidiosa biosensor that assesses DSF-dependent expression of hxfA or hxfB revealed a high level of molecular specificity of DSF signaling. IMPORTANCE X. fastidiosa causes diseases in many important plants, including grape, where it incites Pierce’s disease. Virulence of X. fastidiosa for grape is coordinated by cell-cell signaling molecules, designated DSF (Diffusible Signaling Factor). Mutants blocked in DSF production are hypervirulent for grape, suggesting that virulence is suppressed upon DSF accumulation and that disease could be controlled by artificial elevation of the DSF level in plants. In this work, we describe the isolation of the DSF produced by X. fastidiosa and the verification of its biological activity as an antivirulence factor. We also have developed X. fastidiosa DSF biosensors to evaluate the specificity of cell-cell signaling to be investigated.